- Keakuratan Kode Diagnosis Penyakit Berdasarkan ICD-10 Pasien Rawat Inap Di Rumah Sakit Cakra Husada Klaten: - - Haryo Nugroho (Politeknik Kesehatan Permata Indonesia Yogyakarta, 2021)
Abstract Background :. The coding should be carried out by medical record officers who have competence related to the classification and codification of diseases in accordance with the Minister of Health Regulation No. 55 of 2013 concerning the Implementation of Medical Recorder Jobs. The accuracy of the diagnosis code in the medical record file is used as the basis for making reports. Based on the results of a preliminary study conducted by researchers, the determination of the disease diagnosis code is not carried out every day in the medical record section but in the insurance section but the medical record officer still performs coding on Sundays and red dates only with the number of outpatients every day about 400 patients and outpatients. hospitalized around 50 patients with a total BOR of 46.5% in 2020. Based on this background, researchers are interested in conducting research on